2017
DOI: 10.1097/sla.0000000000002391
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Outcomes of Minimally Invasive Gastrectomy Versus Open Gastrectomy During the Early Introduction of Minimally Invasive Gastrectomy in the Netherlands

Abstract: MIG was safely introduced in the Netherlands, with overall morbidity and mortality comparable with OG, less wound complications and shorter hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
44
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 21 publications
9
44
3
4
Order By: Relevance
“…The difference was mainly caused by the decrease in local complications, not by systemic complications; in particular, the incidence of fluid collection and intra-abdominal bleeding was significantly lower with laparoscopic gastrectomy than with open surgery. The postoperative morbidity rates of laparoscopic gastrectomy range from 6.4 % to 24.2 % [5,11,12,15,16,24]. In the current study, the morbidity rate was 16%, which is within the range reported previously, indicating that the morbidity rate in our study is satisfactory.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The difference was mainly caused by the decrease in local complications, not by systemic complications; in particular, the incidence of fluid collection and intra-abdominal bleeding was significantly lower with laparoscopic gastrectomy than with open surgery. The postoperative morbidity rates of laparoscopic gastrectomy range from 6.4 % to 24.2 % [5,11,12,15,16,24]. In the current study, the morbidity rate was 16%, which is within the range reported previously, indicating that the morbidity rate in our study is satisfactory.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, the reoperation rate in our study was better than that of a study in Italy, which reported a reoperation rate of 9.52% [27]. According to the literature, mortality rates range from 0% to 6% [5,11,22,24]. In our study, there were two mortalities (8%), which is slightly higher than in previous studies.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In parallel, the proportion of laparoscopic resections has increased in some European countries. Thus, in a population-based study conducted in hospitals in the Netherlands, Brenkman et al 2017 reported that the percentage of laparoscopic gastric resections had increased from 4 % in 2011 to 53 % in 2015 [16].…”
Section: Discussionmentioning
confidence: 99%